Radiologic Classification of Superior Canal Dehiscence. Issue 1 (January 2015) - Lookabaugh, Sarah; Kelly, Hillary R.; Carter, Margaret S.; Niesten, Marlien E.F.; McKenna, Michael J.; Curtin, Hugh; Lee, Daniel J.
<x xml:space="preserve">Abstract</x> Objective Surgical access to repair a superior canal dehiscence (SCD) is influenced by the location of the bony defect and its relationship to surrounding tegmen topography as seen on computed tomography. There are currently no agreed-upon methods of characterizing these radiologic findings. We propose a formal radiologic classification system of SCD based on dehiscence location and adjacent tegmen topography. Study Design Retrospective case review Setting Tertiary, neurotology referral center Patients We identified 298 patients with superior canal dehiscence on CT from February 2001 to October 2013. Of these, 251 had symptomatic superior canal dehiscence syndrome and were included in the study. Intervention Patients underwent high-resolution temporal bone CT scans with creation of axial, coronal, Pöschl, and Stenver reformatted images to examine the superior semicircular canal. Two residents-in-training and a head and neck radiologist independently read the scans. Main Outcome Measures CT scans were assessed for (1) superior canal dehiscence or "near" dehiscence, (2) defect location relative to the skull base, (3) surrounding tegmen defects, (4) geniculate ganglion dehiscence, (5) superior petrosal sinus-associated dehiscence (SPS), (6) low-lying tegmen, and (7) the distance between the outer table of the temporal bone and the arcuate eminence.